Redefining the scope of agent's authority / Hazleen Ismail - Ismail, Hazleen (Faculty of Law, 1986)
The Law of Agency introduces a situation whereby n person can act on behalf of another end thus enter into a contract on behalf of that person with a third party' creating ac ontractual relationship and obligations between those two parties. This subsisting relationship will then bind both the third party and the other person he purported to act for.In such a situation, the person who acts on behalf of the other in called the 'agent' and the person for whom and on whose behalf the act was done is called the 'principal'.The Contracts Act, 1950 ("Revised 1974) under Section 135 provides:“An agent is a person employed to do any act for another in dealings with third persons. The person for whom such act is done, or who is so represented, is called the principal"There is however no definite or exact definition as to the word ' Agency'. But in attempting to give a definition to it,authors and judges have taken a stand that there must exist authority given by the principal to his agent which can alter the principal’s legal relation with a third party.